Recent advances in bio-inspired ionic liquid-based interfacial materials from preparation to application - Zhang, Zhe; Zhao, Ran; Wang, Shutao; Meng, Jingxin (Frontiers in Bioengineering and Biotechnology, 2023)
Natural creatures always display unique and charming functions, such as the adhesion of mussels and the lubrication of Nepenthes, to maintain their life activities. Bio-inspired interfacial materials infused by liquid, especially for ionic liquids (ILs), have been designed and prepared to meet the emerging and raising needs of human beings. In this review, we firstly summarize the recent development of bio-inspired IL-based interfacial materials (BILIMs) ranging from the synthesis strategy to design principle. Then, we discuss the advanced applications of BILIMs from anti-adhesive aspect (e.g., anti-biofouling, anti-liquid fouling and anti-solid fouling) to adhesive aspect (e.g., biological sensor, adhesive tape and wound dressing). Finally, the current limitations and future prospects of BILIMs are provided to feed the actual needs.